First tiger shark Galeocerdo cuvier bite in 75 years in French Polynesia (Eastern Central Pacific). Issue 1 (16th January 2023) - Clua, Eric E. G.; Bègue, Michel; Jam, Olivier; Lambillon, Raphaël; Meyer, Carl G.
Abstract: We analyzed a tiger shark (estimated 2.8 m total length) bite on a snorkeler. The removal of the terminal part of the leg suggests a predatory motivation for the bite. This is the first documented bite by a tiger shark in French Polynesia waters for the past 75 years. Abstract : When sharks bite humans, the removal of large pieces of flesh or bones indicates a feeding motivation. The shark size can be assessed through average interdental distances. Prompt and effective emergency first‐aid measures are crucial for survival.